Meningkatkan kompetensi pedagogik guru SDN 2 Sambongrejo dalam mengembangkan indikator dan instrumen penilaian melalui supervisi klinis di semester I tahun pelajaran 2019/2020 - Suntari Suntari (Universitas Sebelas Maret, 2020)
Abstract. the purposes of this research are to increase and analyze the increasing of 2 Sambongrejo Elementary School teachers’ pedagogical competency in developing the indicators and evaluation instruments through clinical supervision on the First Semester of the 2019/2020 Year Academic. The type of this research is a School Action Research (SAR). This research is held on 2 Sambongrejo Elementary School, Sub district of Tunjungan, Regency of Blora. This research is going on the middle First Semester of the 2019/2020 Year Academic. The instruments of collecting data of this research are the sheets of observation, the sheets of questioner and camera application on the cell phone. Technique of analyzing data of this research is comparative description. The procedure of this research is using Cycle Model. The conclusion of this research is 2 Sambongrejo Elementary School teachers’ pedagogical competency in developing the indicators and evaluation instruments through clinical supervision on the First Semester of the 2019/2020 Year Academic increased from low category (D) become high category (B). On the Early Condition, pedagogical competency in developing the indicators and evaluation instruments included as low category (D). On the First Cycle, pedagogical competency in developing the indicators and evaluation instruments included as moderate category (C). On the Second Cycle, pedagogical competency in developing the indicators and evaluation instruments included as high category (B). Kata kunci: teacher competencies, instrument, supervision, elementary school